Meningkatkan Pemahaman Penggunaan Antibiotik dan Pencegahan Resistensi pada Siswa Kelas X SMA Gajah Mada Bandar Lampung - Satria Wijaya; Anisa Fakhira; Ayu Lestari; Esti Raditiya Putri; Fadholi Ahmad Ismail; Fika Nilam Cahya (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Inappropriate use of antibiotics is one of the main causes of bacterial resistance, which can have serious implications for public health. Adolescents, as a productive and active age group, often make mistakes in using antibiotics due to a lack of sufficient knowledge. This study aims to evaluate the effectiveness of antibiotic usage counseling in increasing the knowledge of 10th-grade students at SMA Gajah Mada Bandar Lampung. The study uses a quasi-experimental approach with a one-group post-test design, accompanied by an initial survey through interviews. Counseling was carried out using interactive lectures, group discussions, presentation media, leaflets, and educational games. The sample consisted of 30 10th-grade students. The results of the study showed a significant increase in knowledge after the counseling, with an average post-test score of 98.33%. As many as 83.33% of respondents achieved perfect scores on the post-test. These findings indicate that antibiotic usage counseling is effective in improving students' knowledge regarding the proper use of antibiotics and the prevention of bacterial resistance. This result is important as a basis for developing broader educational programs to reduce the risk of antibiotic resistance among adolescents.